Synthesis of dipeptide benzoylalanylglycine methyl ester and corrosion inhibitor evaluation by Tafel equation - Juniarti Abdurrahman,; Deana Wahyuningrum,; Sadijah Achmad,; Bumbun Bundjali, (Universiti Kebangsaan Malaysia, 2011)
Corrosion is one of the major problems in petroleum mining and processing industry. The pipelines used to transport crude oil from reservoir to the processing installation were made from carbon steel that is susceptible towards corrosion. One of the best methods to prevent corrosion that occurred at the inner parts of carbon steel pipelines is to use organic corrosion inhibitor. One of the potent organic corrosion inhibitors is amino acids derivatives. In this study, dipeptide compound namely benzoylalanylglycine methyl ester and benzoylalanylglycine have been synthesized. The structure elucidation of the products was performed by IR, MS and NMR spectroscopy. The determination of corrosion inhibition activity utilized the Tafel method. The corrosion inhibition efficiency of glycine methyl ester, benzoylalanine, dipeptide benzoylalanylglycine methyl ester and dipeptide benzoylalanylglycine were 63.34%, 35.86%, 68.40% and 27.72%, respectively. These results showed that the formation of dipeptide benzoylalanylglycine methyl ester, derived from carboxylic protected glycine and amine protected alanine, increased the corrosion inhibition activity due to the loss of acidity center in the structure of glicine and L-alanine that would induce the corrosive environment towards carbon steel.